Ultralow-temperature strong ultraviolet radiation-resistant flexible lightweight thermoelectric material and preparation method thereof

By treating the macrocarbon nanotube film in extreme environments, a flexible and lightweight thermoelectric material with ultra-low temperature resistance to strong ultraviolet radiation was prepared, which solved the problem of low power factor of thermoelectric materials in the prior art in extreme environments, and achieved efficient thermoelectric conversion and long-term stability.

CN119873803AActive Publication Date: 2025-04-25XI AN JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510101293.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Existing thermoelectric materials exhibit low power factors under ultra-low temperature and strong ultraviolet radiation conditions, making it difficult to meet the power requirements in extreme environments such as Arctic/Antarctic exploration or deep space exploration.

Method used

Macroscopic carbon nanotube films were synthesized by floating catalyst chemical vapor deposition method, and ultra-low temperature, strong ultraviolet radiation-resistant flexible and lightweight thermoelectric materials were prepared by heat treatment, hydrochloric acid and chlorosulfonic acid treatment.

Benefits of technology

At 100K, the thermoelectric power factor reaches 7.3mW m-1K-2, with good flexibility and mechanical strength, can maintain high stability for more than 108 hours under ultraviolet radiation of 254/365nm, and exhibit high thermoelectric conversion ability at ultra-low temperatures, with a weight output power density of up to 5730μW g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005254254860000011
    Figure HDA0005254254860000011
  • Figure HDA0005254254860000012
    Figure HDA0005254254860000012
  • Figure HDA0005254254860000013
    Figure HDA0005254254860000013
Patent Text Reader

Abstract

The invention discloses an ultralow-temperature strong-ultraviolet-radiation-resistant flexible lightweight thermoelectric material and a preparation method thereof. The preparation method comprises the following steps: synthesizing a macroscopic carbon nanotube film by using a floating catalyst chemical vapor deposition method; the macroscopic carbon nanotube film is subjected to heat treatment and hydrochloric acid and chlorosulfonic acid treatment, and the ultralow-temperature strong ultraviolet radiation resistant flexible lightweight thermoelectric material is obtained. The carbon nanotube film prepared by the invention is treated by hydrochloric acid and chlorosulfonic acid, the thermoelectric power factor can be kept at 7.3 mW m <-1 > K <-2 > at 100K, and the high stability can be kept for more than 108h under the ultraviolet radiation of 254 / 365nm. The processed carbon nanotube film is assembled into a single-leg thermoelectric power generation device, and the thermoelectric conversion capability of the film at an ultralow temperature is proved, and the weight output power density of the film is as high as 5730 [mu] W g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermoelectric energy conversion, and relates to a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation, and a preparation method thereof. Background Art

[0002] Developing new renewable energy sources and improving energy efficiency have become important directions for the development of science and technology today. In extreme environments and special applications, such as Arctic / Antarctic exploration or deep space exploration under ultra-low temperature and strong ultraviolet radiation conditions, reliable power sources are very much needed [Nat. Mater. 17, 846-850 (2018); Adv. Mater. 36, 2400020 (2024)]. High-performance thermoelectric power generation devices can achieve direct energy conversion between thermal energy and electrical energy through an all-solid-state structure. The power generation device has a simple structure, does not require liquid flow and moving parts, is noiseless, can work for a long time, and has no emissions or pollution, making it highly reliable in these applications [Adv. Energy Mater. 11, 2100920 (2021); Nat. Mater. 21, 503-513 (2022)]. In addition, unlike photovoltaic devices [Nat. Nanotechnol. 9, 126-130 (2014); Adv. Mater. 30, 1707271 (2018); Science 360, 904-907 (2018)], since they can operate in the absence of light, they expand the application scope of thermoelectric power generation in dark environments such as the Arctic / Antarctic polar night and deep space conditions.

[0003] Traditional thermoelectric devices are mostly made of inorganic materials. Although these materials have high thermoelectric performance, they usually have problems such as high cost, heavy weight, material toxicity, and poor environmental stability [Nano Energy 121, 109213 (2024); Joule 3, 53-80 (2019)], such as tellurium, bismuth [Nat. Commun. 14, 4932 (2023); J. Mater. Chem. C 11, 4056-4069 (2023); Nano Energy 126, 109651 (2024)], etc. Organic thermoelectric materials are flexible and lightweight, but their performance is not as good as that of inorganic materials, and their operating temperature is usually limited to around 300K or slightly higher [Nat. Commun. 9, 3817 (2018); Nano Energy 80, 105488 (2021)]. Therefore, exploring flexible, lightweight and high power factor thermoelectric materials has become a research hotspot in the thermoelectric field [Science 377, 854-858 (2022); Adv. Mater. 31, 1807916 (2019); Adv. Energy Mater. 10, 1902842 (2020)], and the preparation of materials that can be used in extreme environments such as low temperature and ultraviolet radiation remains challenging [Adv. Funct. Mater. 31, 2104071 (2021)].

[0004] With the development of nanotechnology, low-dimensional nanostructured materials such as carbon nanotubes (CNTs) can simultaneously achieve high power factor, light weight and flexibility [Adv. Funct. Mater. 32, 2203080 (2022); Nat. Commun. 12, 4931 (2021); Nat. Commun. 14, 380 (2023)]. Due to the narrow carrier distribution caused by quantum confinement, significant progress has been made in improving the thermoelectric power factor of one-dimensional / two-dimensional nanomaterials. In some studies, a larger power factor has been achieved, for example, the power factor of single-layer graphene is 36.6mW m -1 K -2

P.Natl.Acad.Sci.113,14272-14276(2016)

Jpn.J.Appl.Phys.58,075003(2019)

Adv.Funct.Mater.32,2111435(2022)

[0005] In order to overcome the problem of low power factor of thermoelectric materials in the prior art, the purpose of the present invention is to provide a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation and a preparation method thereof.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation comprises the following steps:

[0008] Synthesis of macroscopic carbon nanotube films by floating catalyst chemical vapor deposition;

[0009] The macroscopic carbon nanotube film is treated with heat, hydrochloric acid and chlorosulfonic acid to obtain a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation.

[0010] Furthermore, macroscopic carbon nanotube films are prepared by the following process:

[0011] dissolving ferrocene and thiophene in n-hexane and methanol to obtain a precursor solution;

[0012] The precursor solution is injected into a reactor at 1573-1773K, and then the precursor solution is sent into the high temperature zone of a horizontal furnace by nitrogen to obtain carbon nanotube aerogel;

[0013] The carbon nanotube aerogel is pressurized to obtain a macroscopic carbon nanotube film.

[0014] Furthermore, the molar ratio of ferrocene to thiophene is 5.72:1, the volume ratio of n-hexane to methanol is 1:4, and the dosage ratio of ferrocene to n-hexane is 14.3 mmol:14 mL.

[0015] Furthermore, the temperature in the high temperature zone is 1573-1773K.

[0016] Furthermore, the pressurizing pressure is 4-5 tons and the time is 5-10 minutes.

[0017] Further, the macroscopic carbon nanotube film is treated by heat treatment, hydrochloric acid and chlorosulfonic acid to obtain a flexible lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation, including the following steps:

[0018] The macroscopic carbon nanotube film is heated at a temperature of 1173-1373K in an inert atmosphere for 16-18h, then soaked in hydrochloric acid and dried, and then densified with chlorosulfonic acid at 323-523K to form CNT treated film;

[0019] CNT treated The film is dedoped under nitrogen protection to obtain a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation.

[0020] Furthermore, the mass concentration of the hydrochloric acid is 36-38%, and the soaking time is 1 to 4 hours.

[0021] Furthermore, the dedoping treatment is performed at a temperature of 373K-1273K and a time of 15min-120min.

[0022] A flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation.

[0023] Furthermore, in a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the ultra-low temperature and strong ultraviolet radiation resistant flexible lightweight thermoelectric material is as high as 5730μW g -1 .

[0024] Compared with the prior art, the present invention has significant beneficial effects:

[0025] In the present invention, the macroscopic carbon nanotube film is treated by heat treatment, hydrochloric acid and chlorosulfonic acid to obtain a flexible and lightweight thermoelectric material with ultra-low temperature and strong ultraviolet radiation resistance, which has a power of 7.3 mW m at 100K. -1 K -2 The high thermoelectric power factor is at a relatively high level among the most advanced p-type flexible thermoelectric materials at ultra-low temperatures. The ZT of the present invention after acid treatment is almost independent of temperature and is close to the ZT of some inorganic materials at ultra-low temperatures, such as CePd 2.95(~0.17 at 150K) and Ce(Ni 0.8 Cu 0.2 )Al3 (~0.04 at 150K). The flexible and lightweight thermoelectric material shows excellent flexibility at ultra-low temperatures. When the tweezers are swung, the film can still fluctuate in liquid nitrogen. The conductivity and Seebeck coefficient can be restored by rapid heating in the range of 77 to 300K. After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the carbon nanotube film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the carbon nanotube film is as high as 5730μW g -1 , with good thermoelectric conversion capability. The results show that carbon nanotube films have potential applications under ultra-low temperature and strong ultraviolet radiation conditions, such as Arctic / Antarctic exploration or deep space exploration. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Mechanism diagram for preparing carbon nanotube films with ultra-low temperature and strong ultraviolet radiation resistance.

[0027] Figure 2 Schematic diagram of the synthesis of carbon nanotube films.

[0028] Figure 3 The CNT prepared in Example 1 as-syn SEM images of the film, where (a) is the morphology at low magnification, (b) is the morphology at high magnification, (c) is the cross-section at low magnification, and (d) is the cross-section at high magnification.

[0029] Figure 4 The CNT prepared in Example 1 treated SEM images of the film, where (a) is the morphology at low magnification, (b) is the morphology at high magnification, (c) is the cross-section at low magnification, and (d) is the cross-section at high magnification.

[0030] Figure 5 The CNT prepared in Example 1 treated-H / 30 SEM images of the film, where (a) is the morphology at low magnification, (b) is the morphology at high magnification, (c) is the cross-section at low magnification, and (d) is the cross-section at high magnification.

[0031] Figure 6 The CNT prepared in Example 1 treated-H / 30 The curves of film conductivity and Seebeck coefficient changing with temperature.

[0032] Figure 7 The CNT prepared in Example 1 treated-H / 30 Variation of sheet resistance and Seebeck coefficient with liquid nitrogen immersion time.

[0033] Figure 8 The CNT prepared in Example 1 treated-H / 30 Schematic diagram of the film bending experiment in liquid nitrogen and the curve diagram of the change of resistance and Seebeck coefficient with the number of bending times, where (a) is the bending experiment diagram and (b) is the change curve diagram.

[0034] Fig. 9 The CNT prepared in Example 1 treated-H / 30 The ultraviolet light irradiation experiment diagram of the film and the change curve diagram of resistance and Seebeck coefficient with ultraviolet light irradiation, where (a) is the ultraviolet light irradiation experiment diagram and (b) is the change curve diagram.

[0035] Fig.10 The CNT prepared in Example 1 treated-H / 30 Schematic diagram of the thin film output performance test and a comparison diagram of the surface output power density and weight output power density of the thermoelectric device at different temperature differences with the macroscopic flexible thermoelectric devices in the literature, where (a) is the output performance test diagram and (b) is the comparison diagram of the surface output power density and weight output power density of the thermoelectric device.

[0036] Fig.11 The CNT prepared in Example 1 treated-H / 30 Comparison of the comprehensive performance of the film and p-type thermoelectric films reported in the literature. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0038] See also Figure 1 and Figure 2 The present invention provides a method for preparing a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation. The method uses a floating catalyst chemical vapor deposition (FCCVD) method to synthesize a highly conductive macroscopic carbon nanotube film, which is then treated with high temperature, hydrochloric acid and chlorosulfonic acid (CSA). The method specifically includes the following steps:

[0039] (1) Synthesize carbon nanotube aerogel in a horizontal furnace, use nitrogen as carrier gas, nitrogen flow rate is 0.5L / min~1L / min, dissolve ferrocene and thiophene in n-hexane and methanol, treat with ultrasound for 30min, prepare precursor solution, inject the precursor solution into the reactor (horizontal furnace at 1573~1773K) at a rate of 0.5~3ml / min, then bring the precursor solution into the high temperature zone of the horizontal furnace with nitrogen flow rate of 0.5~15L / min, the temperature of the high temperature zone is 1573~1773K, and obtain carbon nanotube aerogel. Finally, the carbon nanotube aerogel is discharged from the reactor into the air by nitrogen and collected by a drum; wherein, the molar ratio of ferrocene to thiophene is 5.72:1, the volume ratio of n-hexane to methanol is 1:4, and the dosage ratio of ferrocene to n-hexane is 14.3mmol:14mL;

[0040] (2) The carbon nanotube aerogel prepared in step (1) is collected using a winding drum with a diameter of 10 cm, and the winding drum is wrapped with a sulfate paper substrate. During the preparation process, the winding rate is adjusted to 1-5 mm / s. A certain amount of methanol is sprayed during the collection process. After collecting for 30 minutes, the film is peeled off from the drum. Then, a tablet press (Kejing MSK-2150, China) is used to compress the film with a force of 4-5 tons for 5-10 minutes to make the surface of the film smooth and dense, thereby preparing CNT as-syn membrane;

[0041] (3) Place the CNT as-syn The film is placed in a tube furnace and heated in an inert atmosphere at 1173-1373K for 16-18h, then soaked in concentrated hydrochloric acid for 1-4h; the film treated with concentrated hydrochloric acid (mass concentration of 36-38%) for 1-4h is soaked in deionized water three times and then dried in air at room temperature. After drying, the film is immersed in CSA at 323-523K to densify the film and form CNTs. treated film;

[0042] (4) Place the CNT treated The film is heated under nitrogen protection with a nitrogen flow rate of 0.01 L / min to optimize the acid doping level under different working conditions. Specifically, dedoping is performed at different temperatures of 373K-1273K for 15min-120min. Preferably, acid doping is performed at (373K, 573K, 773K, 973K and 1273K, with a dedoping time of 30min) and (dedoping temperature of 773K, with a dedoping time of 15min, 30min, 60min, 120min) to obtain an optimized CNT film, i.e., the flexible lightweight thermoelectric material, and form a single-leg thermoelectric power generation device.

[0043] During the test of the thermoelectric power generation device, the change of the cold end temperature was adjusted by liquid nitrogen, and the hot end temperature was controlled at about 303K by the heater. The output voltage was obtained using a Keithley 2400 multimeter.

[0044] (5) Performance test: The Seebeck coefficient and conductivity were measured using commercial equipment (NETZSCH SBA-458, Germany). The conductivity was measured using the four-probe method. The Seebeck coefficient and conductivity were obtained simultaneously using a bidirectional heating test method. The thermal conductivity was measured using a commercial instrument (VTET-01). Three or more samples were tested for each data point. Two different types of ultraviolet light with wavelengths of 254 nm and 365 nm were used to simulate the outer space environment or ultraviolet light exposure at high altitudes.

[0045] Scanning electron microscope (SEM) images were obtained by FEIQUANTA 250FEG from USA.

[0046] Transmission electron microscopy (TEM) images were obtained using a Japanese JEOL 2010D with an accelerating voltage of 200 KV.

[0047] Thermogravimetric analysis (TGA) of the carbon nanotube film was performed using an American synchronous thermal analyzer Q600 in an air atmosphere at a heating rate of 10°C / min.

[0048] X-ray photoelectron spectroscopy was performed by ThermoFisher Scientific ESCALAB Xi+, USA.

[0049] Raman spectra were recorded using an American ThermoFisher Raman spectrometer with an excitation wavelength of 514 nm. Conductivity was obtained using a four-probe method.

[0050] The following are specific embodiments.

[0051] Example 1

[0052] (1) Synthesize carbon nanotube aerogel in a horizontal furnace, using nitrogen as carrier gas at a nitrogen flow rate of 0.5 L / min. Dissolve ferrocene and thiophene in a mixture of n-hexane and methanol to prepare a precursor solution. The molar ratio of ferrocene to thiophene is 5.72:1, the volume ratio of n-hexane to methanol is 1:4, and the dosage ratio of ferrocene to n-hexane is 14.3 mmol:14 mL. Treat with ultrasound for 30 min, inject the precursor solution into the reactor (horizontal furnace at 1673 K) at a rate of 1.5 ml / min, and then bring it into the high temperature zone of the horizontal furnace with nitrogen at a flow rate of 5 L / min. Finally, the carbon nanotube aerogel is discharged from the reactor into the air by nitrogen and collected by a drum;

[0053] (2) The carbon nanotube aerogel prepared in step (1) is collected using a winding drum with a diameter of 10 cm, and the winding drum is wrapped with a sulfate paper substrate. During the preparation process, the winding rate is adjusted to 3 mm / s. A certain amount of methanol is sprayed during the collection process. After collecting for 30 minutes, the film is peeled off from the drum. Then a tablet press (Kejing MSK-2150 China) is used to compress the film with a force of 4 tons for 5 minutes to make the surface of the film smooth and dense, and the CNT as-syn membrane;

[0054] (3) Place the CNT as-syn The film was placed in a tube furnace and heated in an inert atmosphere at 1273K for 16h, then treated with concentrated hydrochloric acid for 2h; the film treated with concentrated hydrochloric acid was soaked in deionized water for about 3 times and then dried in air at room temperature. After drying, the film was densified with CSA at 423K to form CNTs. treated film;

[0055] (4) Place the CNT treated The film was heated under nitrogen protection with a flow rate of 0.01 L / min at 973 K for CNT treated The film was heated for 30 min to obtain CNT treated-H / 30 The film is a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation;

[0056] (5) Performance test: using CNT treated-H / 30 The film formed a single-leg thermoelectric power generation device. After irradiation with 254 / 365nm ultraviolet light for 108h, the conductivity and Seebeck coefficient of the film remained unchanged. Under the single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated carbon nanotube film was 5730μW g -1 .

[0057] See also Figure 3 In (a)-(d), we can see that CNT as-syn The surface of the film is porous, with diameters of hundreds of nanometers.

[0058] The thickness is about 1.3μm.

[0059] See also Figure 4 In (a)-(d), we can see that CNT treated The film thickness is about 250nm. as-syn Compared with the film surface, CNT treated The film surface is smoother and tighter.

[0060] See also Figure 5 In (a)-(d), we can see that CNT treated-H / 30Compared with unheated CNT treated Compared with the thin film, the surface becomes porous and has holes. treated-H / 30 The film thickness also increased slightly from about 250nm to about 300nm, which also led to the CNT treated The density of the film ranged from 2.01 g cm -3 Down to 1.16 g cm -3 .

[0061] See also Figure 6 , it can be seen that when the temperature decreases from 300K to 100K, the CNT treated-H / 30 The conductivity of the film increases and the Seebeck coefficient decreases. At a low temperature of 100K, the treated CNT treated The film can obtain 7.3mW m -1 K -2 High power factor.

[0062] See also Figure 7 , it can be seen that CNT treated-H / 30 When the film is stored in liquid nitrogen for about 4 hours, its conductivity and Seebeck coefficient remain almost unchanged.

[0063] See also Figure 8 In (a) and (b), it can be seen that CNT treated-H / 30 The film can be bent freely, and the sample can be bent nearly 180° at a bending curvature of 3 mm in diameter. treated-H / 30 The film exhibits excellent bending stability at ultra-low temperatures. After 1,000 bends, the resistance and Seebeck coefficient show no significant attenuation or fluctuation compared to the original values.

[0064] See also Fig. 9 In (a) and (b), it can be seen that CNT treated-H / 30 After 108 hours of UV irradiation, the conductivity and Seebeck coefficient of the film remained stable. treated-H / 30 The film has good UV resistance.

[0065] See also Fig.10 In (a) and (b), it can be seen that the CNT with a width of 5 mm and a length of 40 mm treated-H / 30 The maximum output power density of the single-leg thermoelectric device normalized by weight and area is 5730 μW g -1 and 1140W m -2 .

[0066] See also Fig.11 , it can be seen that CNT treated-H / 30The film not only has high thermoelectric performance at ultra-low temperatures, but also has excellent flexibility, good mechanical strength and low density. It is a high-performance, multifunctional lightweight film. treated-H / 30 The membrane also has the characteristics of strong water resistance, rapid temperature changes, and long-term ultraviolet radiation.

[0067] The results show that CNT treated-H / 30 Thin films are ideal materials for manufacturing highly integrated thermoelectric power generation devices and have potential applications in extreme environments such as Arctic / Antarctic expeditions or deep space exploration.

[0068] Example 2

[0069] (1) The preparation was consistent with Example 1. Except that the ultrasonically treated precursor solution was injected into the reactor, the temperature of the reactor was changed from 1673K to 1773K.

[0070] (2) The preparation was consistent with Example 1.

[0071] (3) The preparation was consistent with Example 1.

[0072] (4) The preparation was consistent with Example 1.

[0073] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 5510μW g -1 .

[0074] Example 3

[0075] (1) The preparation was consistent with Example 1. Except that the ultrasonically treated precursor solution was injected into the reactor, the temperature of the reactor was changed from 1673K to 1573K.

[0076] (2) The preparation was consistent with Example 1.

[0077] (3) The preparation was consistent with Example 1.

[0078] (4) The preparation was consistent with Example 1.

[0079] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4530μW g -1 .

[0080] Example 4

[0081] (1) The preparation was consistent with Example 1.

[0082] (2) The preparation was consistent with Example 1.

[0083] (3) The preparation was consistent with Example 1.

[0084] (4) The preparation was the same as in Example 1. treated The film was heated to 1173K.

[0085] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4930μW g -1 .

[0086] Example 5

[0087] (1) The preparation was consistent with Example 1.

[0088] (2) The preparation was consistent with Example 1.

[0089] (3) The preparation was consistent with Example 1.

[0090] (4) Preparation is consistent with Example 1. CNT treated The film was heated to 373K.

[0091] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4280μW g -1 .

[0092] Example 6

[0093] (1) The preparation was consistent with Example 1.

[0094] (2) The preparation was consistent with Example 1.

[0095] (3) The preparation was consistent with Example 1.

[0096] (4) The preparation was the same as in Example 1. treated The film was heated for 10 min instead of 30 min.

[0097] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 3380μW g -1 .

[0098] Example 7

[0099] (1) The preparation was consistent with Example 1.

[0100] (2) The preparation was consistent with Example 1.

[0101] (3) The preparation was consistent with Example 1.

[0102] (4) The preparation was the same as in Example 1. treated The film was heated for 60 min instead of 30 min.

[0103] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4820μW g -1 .

[0104] Example 8

[0105] (1) The preparation was consistent with Example 1, except that the precursor after ultrasonic treatment was injected into the reactor at a rate of 0.5 ml / min instead of 1.5 ml / min.

[0106] (2) The preparation was consistent with Example 1.

[0107] (3) The preparation was consistent with Example 1.

[0108] (4) The preparation was consistent with Example 1.

[0109] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 5540μW g -1 .

[0110] Example 9

[0111] (1) The preparation was consistent with Example 1, except that the precursor after ultrasonic treatment was injected into the reactor at a rate of 3 ml / min instead of 1.5 ml / min.

[0112] (2) The preparation was consistent with Example 1.

[0113] (3) The preparation was consistent with Example 1.

[0114] (4) The preparation was consistent with Example 1.

[0115] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4820μW g -1 .

[0116] Example 10

[0117] (1) The preparation was consistent with Example 1.

[0118] (2) The preparation was consistent with Example 1.

[0119] (3) The preparation is consistent with Example 1. In addition, the prepared CNT as-syn The film was heated in a tube furnace at 1273 K under inert atmosphere and then at 1173 K.

[0120] (4) The preparation was consistent with Example 1.

[0121] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 3680μW g -1 .

[0122] Embodiment 11

[0123] (1) The preparation was consistent with Example 1.

[0124] (2) The preparation was consistent with Example 1.

[0125] (3) The preparation is consistent with Example 1. In addition, the prepared CNT as-syn The film was heated in a tube furnace at 1273 K under inert atmosphere and then at 1373 K.

[0126] (4) The preparation was consistent with Example 1.

[0127] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4930μW g -1 .

[0128] Example 12

[0129] (1) The preparation was consistent with Example 1.

[0130] (2) The preparation was consistent with Example 1.

[0131] (3) The preparation was the same as in Example 1, except that the treatment with concentrated hydrochloric acid was changed from 2 h to 1 h.

[0132] (4) The preparation was consistent with Example 1.

[0133] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4435μW g -1 .

[0134] Example 13

[0135] (1) The preparation was consistent with Example 1.

[0136] (2) The preparation was consistent with Example 1.

[0137] (3) The preparation was the same as in Example 1, except that the treatment with concentrated hydrochloric acid was changed from 2 h to 4 h.

[0138] (4) The preparation was consistent with Example 1.

[0139] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 3690μW g -1 .

[0140] Embodiment 14

[0141] (1) The preparation was consistent with Example 1.

[0142] (2) The preparation was consistent with Example 1.

[0143] (3) The preparation was the same as in Example 1, except that the densification at 423 K was changed to 323 K.

[0144] (4) The preparation was consistent with Example 1.

[0145] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 4670μW g -1 .

[0146] Embodiment 15

[0147] (1) The preparation was consistent with Example 1.

[0148] (2) The preparation was consistent with Example 1.

[0149] (3) The preparation was the same as in Example 1, except that the densification at 423 K was changed to 523 K.

[0150] (4) The preparation was consistent with Example 1.

[0151] (5) Performance test: After irradiation with 254 / 365nm UV light for 108h, the conductivity and Seebeck coefficient of the film remain unchanged. Under a single-leg device with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the treated CNT film is 3895μW g -1 .

[0152] Embodiment 15

[0153] (1) Synthesize carbon nanotube aerogel in a horizontal furnace, using nitrogen as carrier gas at a nitrogen flow rate of 1 L / min. Dissolve ferrocene and thiophene in a mixture of n-hexane and methanol to prepare a precursor solution. The molar ratio of ferrocene to thiophene is 5.72:1, the volume ratio of n-hexane to methanol is 1:4, and the dosage ratio of ferrocene to n-hexane is 14.3 mmol:14 mL. Treat with ultrasound for 30 min, inject the precursor solution into the reactor (horizontal furnace at 1600 K) at a rate of 1 ml / min, and then bring it into the high temperature zone of the horizontal furnace with nitrogen at a flow rate of 0.5 L / min. Finally, the carbon nanotube aerogel is discharged from the reactor into the air by nitrogen and collected by a drum;

[0154] (2) The carbon nanotube aerogel prepared in step (1) was collected using a winding drum with a diameter of 10 cm, and the winding drum was wrapped with a sulfate paper substrate. During the preparation process, the winding rate was adjusted to 1 mm / s. A certain amount of methanol was sprayed during the collection process. After collecting for 30 minutes, the film was peeled off from the drum. Then, a tablet press (Kejing MSK-2150, China) was used to compress the film with a force of 5 tons for 5 minutes to make the surface of the film smooth and dense, and the CNT as-syn membrane;

[0155] (3) Place the CNT as-synThe film was placed in a tube furnace and heated in an inert atmosphere at 1210K for 17h, then treated with concentrated hydrochloric acid for 3h; the film treated with concentrated hydrochloric acid was soaked in deionized water for about 3 times and then dried in air at room temperature. After drying, the film was densified with CSA at 380K to form CNTs. treated film;

[0156] (4) Place the CNT treated The film was heated under nitrogen protection with a flow rate of 0.01 L / min at 550 K for CNT treated The film was heated for 15 minutes to obtain an optimized CNT film, i.e., a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation.

[0157] Example 16

[0158] (1) Synthesize carbon nanotube aerogel in a horizontal furnace, using nitrogen as carrier gas at a nitrogen flow rate of 0.8 L / min. Dissolve ferrocene and thiophene in a mixture of n-hexane and methanol to prepare a precursor solution. The molar ratio of ferrocene to thiophene is 5.72:1, the volume ratio of n-hexane to methanol is 1:4, and the dosage ratio of ferrocene to n-hexane is 14.3 mmol:14 mL. Treat with ultrasound for 30 min, inject the precursor solution into the reactor (horizontal furnace at 1700 K) at a rate of 2 ml / min, and then bring it into the high temperature zone of the horizontal furnace with nitrogen at a flow rate of 15 L / min. Finally, the carbon nanotube aerogel is discharged from the reactor into the air by nitrogen and collected by a drum;

[0159] (2) The carbon nanotube aerogel prepared in step (1) is collected using a winding drum with a diameter of 10 cm, and the winding drum is wrapped with a sulfate paper substrate. During the preparation process, the winding rate is adjusted to 5 mm / s. A certain amount of methanol is sprayed during the collection process. After collecting for 30 minutes, the film is peeled off from the drum. Then a tablet press (Kejing MSK-2150 China) is used to compress the film with a force of 4.5 tons for 10 minutes to make the surface of the film smooth and dense, and the CNT as-syn membrane;

[0160] (3) Place the CNT as-syn The film was placed in a tube furnace and heated in an inert atmosphere at 1330K for 18h, then treated with concentrated hydrochloric acid for 2h; the film treated with concentrated hydrochloric acid was soaked in deionized water for about 3 times and then dried in air at room temperature. After drying, the film was densified with CSA at 470K to form CNTs. treated film;

[0161] (4) Place the CNT treatedThe film was heated under nitrogen protection with a flow rate of 0.01 L / min at 870 K for CNT treated The film was heated for 120 minutes to obtain an optimized CNT film, i.e., a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation.

[0162] The present invention synthesizes carbon nanotube aerogel in a nitrogen atmosphere, then uses ultrasonic wave to treat the precursor solution, and then uses heat treatment, hydrochloric acid and chlorosulfonic acid to treat the flexible and lightweight thermoelectric material. The thermoelectric power factor can be maintained at 7.3mW m at 100K. -1 K -2 , can maintain high stability for more than 108 hours under 254 / 365nm ultraviolet radiation, and has good flexibility and mechanical strength. The treated carbon nanotube film was assembled into a single-leg thermoelectric power generation device, demonstrating the film's thermoelectric conversion capability at ultra-low temperatures, with a weight output power density of up to 5730μW g -1 This is very attractive for building highly integrated systems for special applications such as Arctic / Antarctic expeditions or deep space exploration.

[0163] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0164] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation, characterized in that: The following steps are involved: Synthesis of macroscopic carbon nanotube films by floating catalyst chemical vapor deposition; The macroscopic carbon nanotube film is treated with heat, hydrochloric acid and chlorosulfonic acid to obtain a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation.

2. The method for preparing the ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 1, characterized in that: Macroscopic carbon nanotube films are prepared by the following process: dissolving ferrocene and thiophene in n-hexane and methanol to obtain a precursor solution; The precursor solution is injected into a reactor at 1573-1773K, and then the precursor solution is sent into the high temperature zone of a horizontal furnace by nitrogen to obtain carbon nanotube aerogel; The carbon nanotube aerogel is pressurized to obtain a macroscopic carbon nanotube film.

3. The method for preparing the ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 2, characterized in that: The molar ratio of ferrocene to thiophene is 5.72:1, the volume ratio of n-hexane to methanol is 1:4, and the dosage ratio of ferrocene to n-hexane is 14.3 mmol:14 mL.

4. The method for preparing the ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 2, characterized in that: The temperature in the high temperature zone is 1573~1773K.

5. The method for preparing the ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 2, characterized in that: The pressurization pressure is 4-5 tons and the time is 5-10 minutes.

6. The method for preparing the ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 1, characterized in that: The macroscopic carbon nanotube film is treated by heat treatment, hydrochloric acid and chlorosulfonic acid to obtain a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation, including the following steps: The macroscopic carbon nanotube film is heated at a temperature of 1173-1373K in an inert atmosphere for 16-18h, then soaked in hydrochloric acid and dried, and then densified with chlorosulfonic acid at 323-523K to form CNT treated film; CNT treated The film is dedoped under nitrogen protection to obtain a flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation.

7. The method for preparing the ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 6, characterized in that: The mass concentration of hydrochloric acid is 36-38%, and the soaking time is 1 to 4 hours.

8. The method for preparing the ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 6, characterized in that: The temperature of the dedoping treatment is 373K-1273K, and the time is 15min-120min.

9. A flexible and lightweight thermoelectric material that is ultra-low temperature and resistant to strong ultraviolet radiation, prepared according to the method according to any one of claims 1 to 8.

10. The ultra-low temperature and strong ultraviolet radiation resistant flexible and lightweight thermoelectric material according to claim 9, characterized in that: Under a single-leg setup with a heat sink temperature of 93K and a heat source of 303K, the weight output power density of the ultra-low temperature and strong ultraviolet radiation-resistant flexible lightweight thermoelectric material is as high as 5730μW g -1 .

Citation Information

Patent Citations

  • Extremely tolerant carbon nanotube hydrogel, and preparation method and application thereof

    CN111841456A

  • Post-treatment method for greatly improving performance of carbon nanotube film and application

    CN116281963A

  • Preparation method of densified carbon nanotube film with low infrared emissivity

    CN119100374A

  • Flexible thermoelement comprising carbon nanotube strand, preparation method thereof

    KR1020180052269A

  • Balanced speaker with a structure that prevents the deformation of an armature

    KR102167447B1